Integration of High-Torque DC Gear Motor Shaft in Wet-based Solar Panel Cleaning System - Zuhaili, Amirul Akmal; Syed Zahurul Islam (Evolution in Electrical and Electronic Engineering, 2023)
This paper proposes an integration of a high-torque DC gear motor shaft in a wet-based solar panel cleaning system. Maintaining the performance of the solar panel by cleaning it regularly is vital to gain the maximum power output from the sun. Bird droppings, dry dust and dirt are inevitably built up on the solar panel. These factors will cause a sharp reduction in the performance and power efficiency of solar panels. The system’s performance was evaluated through testing and the data are recorded. A DC gear motor is used to rotate the cleaning brush at high torque. The analysis of the DC gear motor is conducted to get the parameters suitable for the cleaning brush. The high torque DC gear motor successfully rotates the brush at the speed of 285.5 rpm with a torque of 10Nm. The electrical parameters of speed and current are analysed with the varies of torque and voltage values. The results indicate the current increase in the increase of torque. On the other hand, the increase in voltage will increase the speed of the DC gear motor. Other than that, this project aims to prove the efficiency of the cleaning system by comparing the output value from the solar panel after and before it has been cleaned. Overall, it stated that the performance of the solar panel increases by about 2.93% to 2.73% with regular cleaning.